Evaluation of Urban Flood Control Project –Case Study at Bendung Watershed in Palembang City, Indonesia– - Rian Dinata (Universitas Muhammadiyah Mataram, 2021)
Abstract: Palembang City locates on a lowland where the altitude is between 12 and 30m above sea level. There are many small rivers that flow into a main river, Musi river. Due to the topographical configuration and a seasonal heavy rainfall, those rivers had been overflowed and the city had an inundation disaster. Bendung watershed is one of the nineteen watersheds in Palembang City, and the watershed also experiences the inundation disaster frequently due to the flood caused by a poor river maintenance and drainage system.The local government of Palembang City has applied some flood control projects such as a normalization project to reduce the flood damages. These measures checked the river flow over the dike, but some areas still suffered from the flood damages due to their topography. Based on the current situation, this study evaluates the efficiency of the existing normalization project in this watershed to find a solution that reduces the flood in those areas. Furthermore, this study investigates the feasibility of infiltration-well system to overcome the flood in those areas. The feasibility study includes the cost and benefit analysis to realize the infiltration-well system for easing the inundation problem.Abstrak: Kota Palembang terletak di dataran rendah dengan ketinggian antara 12 sampai 30m di atas permukaan laut. Karena konfigurasi topografi dan curah hujan musiman yang tinggi, sebagian Kota Palembang sangat rentan terhadap genangan dan bencana banjir . DAS Bendung merupakan salah satu dari sembilan belas DAS yang ada di Kota Palembang, dan DAS tersebut juga sering mengalami bencana genangan akibat banjir yang disebabkan oleh sistem drainase yang buruk.Pemerintah Daerah Kota Palembang telah menerapkan beberapa proyek pengendalian banjir seperti proyek normalisasi sungai. Proyek ini cukup sukses mencegah air sungai bendung meluap melewati tanggul sungai tersebut, tetapi beberapa lokasi yang jauh dari sungai bendung masih mengalami genangan karena topografinya. Berdasarkan kondisi ini, studi ini mengevaluasi efisiensi proyek normalisasi di DAS ini untuk mencari solusi yang dapat mengurangi banjir di wilayah tersebut. Selanjutnya studi ini mengkaji kelayakan sistem sumur resapan untuk mengatasi banjir di wilayah tersebut. Studi kelayakan lain meliputi analisis biaya dan manfaat sistem sumur resapan untuk mengatasi masalah genangan.